PGR5-Dependent Cyclic Electron Flow Protects Photosystem I under Fluctuating Light at Donor and Acceptor Sides - Yamamoto, Hiroshi (Plant Physiol, 2019)
In response to a sudden increase in light intensity, plants must cope with absorbed excess photon energy to protect photosystems from photodamage. Under fluctuating light, PSI is severely photodamaged in the Arabidopsis (Arabidopsis thaliana) proton gradient regulation5 (pgr5) mutant defective in the main pathway of PSI cyclic electron transport (CET). Here, we aimed to determine how PSI is protected by two proposed regulatory roles of CET via transthylakoid ΔpH formation: (1) reservation of electron sink capacity by adjusting the ATP/NADPH production ratio (acceptor-side regulation) and (2) down-regulation of the cytochrome b(6)f complex activity called photosynthetic control for slowing down the electron flow toward PSI (donor-side regulation). We artificially enhanced donor- and acceptor-side regulation in the wild-type and pgr5 backgrounds by introducing the pgr1 mutation conferring the hypersensitivity of the cytochrome b(6)f complex to luminal acidification and moss Physcomitrella patens flavodiiron protein genes, respectively. Enhanced photosynthetic control partially alleviated PSI photodamage in the pgr5 mutant background but restricted linear electron transport under constant high light, suggesting that the strength of photosynthetic control should be optimized. Flavodiiron protein-dependent oxygen photoreduction formed a large electron sink and alleviated PSI photoinhibition, accompanied by the induction of photosynthetic control. Thus, donor-side regulation is essential for PSI photoprotection but acceptor-side regulation also is important to rapidly induce donor-side regulation. In angiosperms, PGR5-dependent CET is required for both functions.